Pomological, phenotypical diversity and biochemical characterization of fortheen almond morphotypes from Morocco - Hanine H.; Zinelabidine L.H.; Kodad O.; H'ssaini H.; Haddioui A.; Ennahli S. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
This study was focused on almond germplasm characterization of 14 genotypes from the experimental Ain Taoujadate collection based on morphological, pomological and biochemical traits. Results revealed that Commercial and local (Prunus dulcis L.) cultivars vary considerably in their fruit and kernel characteristics. The majority of important correlations were determined among the fruit traits (length, width, thickness, and weight) and the kernel traits (length, width, thickness, and weight). Morphological dendrogram clustered the genotypes into two main groups. The first group consists of only local accessions. The second group includes, in addition to local genotypes, a mixture of foreign genotypes. The heterogeneous cluster obtained, maybe the cause of an exchange of plant material as seeds between Morocco and other countries.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)